Effect of Moisture Stress on Physiological and Yield Responses of Common Bean Varieties at Lath House Condition, Hawassa University, Southern Ethiopia - Mitike Mulatu Alemu; Andargachew Gedebo; Amsalu Gobena Roro; Tatek Tamiru Geletu (International Journal of Agronomy)
Common bean is one of the most traditional foods, with social and economic importance, and is suitable for food security due to its short growing cycle and adaptability to different cropping systems. However, various constraints like biotic and abiotic factors reported for the low productivity of the crop. Therefore, the study was designed to identify the common bean varieties’ response on physiological properties and yield performance under different irrigation intervals in Lath House condition at Hawassa University, Ethiopia, from June, 2020, to September, 2020. The experiment was laid out in a completely randomized design with a factorial combination of seven common bean varieties (Awash-1, Awash-2, Dursitu, Fedis, Gofta, Nasir, and Tinike) and three moisture levels, eight day irrigation interval, four day irrigation interval, and daily watering with three replication. There was a significant main and interaction effects among the measured parameters. From those significantly affected parameters, the highest stomata numbers (25) were recorded from the Dursitu variety with a daily irrigation interval. The longest stomata aperture was observed with Gofta (133.76 nm) and Fedis varieties (131.13 nm) to daily irrigation and four day irrigation intervals, respectively. A wider stomata aperture was found in the Awash-1(12.6 nm) variety on a daily irrigation interval, and maximum stomata conductance (193.67) was obtained in the Tinike variety treated with a four day irrigation interval. The maximum relative leaf moisture content (96%) was found on the Awash-1 variety at a four day irrigation interval. Maximum water use efficiency was obtained from the Awash-1 (3.95) variety, which is an insignificant variation with the Awash-2 (3.85) and Gofta varieties (3.85) at a four day irrigation interval. Among the varieties, the highest photosynthesis rate (10.43 μmol·m−2·s−1) and transpiration rate (5.42 mmol·m−2·s−1) were obtained in the Gofta variety treated by a four day irrigation interval. In the photosynthetic pigment analysis, the highest leaf chl-a, chl-b, and chl-a + b concentration was recorded at 2.4 μg/ml, 1.53 g/ml, and 3.93 μg/ml, respectively, in the Gofta variety irrigated at a four days interval. The highest (0.586) chlorophyll fluorescence was obtained in the eight day irrigation interval. The highest proline content was found from the Awash-1 (0.78) variety regarding to drought stress condition. The highest pods plant−1 (9) and seed pod−1 (5) was found in the Awash-2 and Awash-1 varieties, respectively, at a four days irrigation interval and the highest main effect of 100 SW (39.48 g), (28.6 g) was found in the Fedis variety and at a four day irrigating interval, respectively. The maximum yield was obtained from the varieties Awash-1 (7.8 g plant−1) and Gofta (7.36 g plant−1) with a four day irrigated interval and they are also superior at drought condition and Awash-2 varieties are enhanced at waterlogging condition as compared to the other varieties.